Representasi Imperialisme Budaya Dalam Video Musik BTS “Dynamite” (Kajian Semiotika Roland Barthes) - Wahyuningratna, Ratu Nadya; M.B.P, Ratu Laura (Universitas Al Azhar Indonesia, 2022)
Music videos are the cultural products that are currently disseminated through the media, especially YouTube. BTS is one of the music groups from South Korea that spreads its music videos through YouTube and reaches more than one billion viewers. This study discusses the representation of cultural hybridity in the Dynamite music video. By using Roland Barthes' semiotic study, it is known that the BTS Dynamite music video contains elements of British, American, and Korean culture. This illustrates the existence of Western cultural imperialism which has turned into Korean cultural imperialism or commonly called Koreanization. Furthermore, this Dynamite music video also illustrates cultural hybridity where the enthusiasm of the people, especially Asians for BTS, is high because of the closeness of values, temporal, historical, and cultural experiences.